2016
DOI: 10.1142/s1758825116500216
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Conformational Evolution of Alpha-Helical BSA Segments on Graphene: A Molecular Dynamics Study

Abstract: Molecular dynamics (MD) simulations are performed to investigate the adsorption mechanics and conformational dynamics of single and multiple bovine serum albumin (BSA) peptide segments on single-layer graphene through analysis of parameters such as the root-mean-square displacements, number of hydrogen bonds, helical content, interaction energies, and motions of mass center of the peptides. It is found that for the single segment system, destabilization of the helical structures in the form of the reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In 2016, Yeo et al ( 2016 ) investigated the adsorption mechanism of single and multiple bovine serum albumin (BSA) peptide segments on G, through the analysis of a broad set of parameters such as root-mean-square displacement, number of hydrogen bonds, helical content, interaction energies, and peptide center-of-mass displacement. The authors observed a destabilization of the helical structures in the single segment system, due to strong interactions between the peptide and the substrate.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…In 2016, Yeo et al ( 2016 ) investigated the adsorption mechanism of single and multiple bovine serum albumin (BSA) peptide segments on G, through the analysis of a broad set of parameters such as root-mean-square displacement, number of hydrogen bonds, helical content, interaction energies, and peptide center-of-mass displacement. The authors observed a destabilization of the helical structures in the single segment system, due to strong interactions between the peptide and the substrate.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…Several previous studies revealed the destruction of α-helix at the surface of graphene and GO and the formation of 3 10 helix and turn. 42–46 Zuo et al reported the adsorption of a Villin headpiece (HP35) on the surface of graphene and carbon nanotube and the loss of its native α-helix structure through strong π–π stacking interactions between graphene and aromatic residues. 47 Here, we have observed a similar strong interactions between the GO and aromatic residue positions such as Trp4, Trp8, Trp11 and Trp15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After interactions with GO sheets, the α -helix contents of BSA and HB decreased to 14.6 and 16.4%, respectively. Our previous work has revealed the binding mechanism of the α -helix fragments of BSA with graphene by using molecular dynamics simulations [ 38 ]. The adsorption of an α -helix on the surface of graphene induces a transition from to the 3 10 -helix structure, which was reflected in the substantial increase in random coils from 24.1 to 42.2% for BSA in this work.…”
Section: Resultsmentioning
confidence: 99%